2013
DOI: 10.1016/j.tate.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The effects of online professional development on higher education teachers' beliefs and intentions towards learning facilitation and technology

Abstract: Please cite as:Rienties, B., Brouwer, N., Lygo-Baker, S. (2013) .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
169
1
20

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 289 publications
(220 citation statements)
references
References 45 publications
7
169
1
20
Order By: Relevance
“…As indicated by previous research (Rienties et al, 2013;Stes et al, 2011), while in educational research amongst students (or even pre-service teachers)…”
Section: Limitationsmentioning
confidence: 70%
See 1 more Smart Citation
“…As indicated by previous research (Rienties et al, 2013;Stes et al, 2011), while in educational research amongst students (or even pre-service teachers)…”
Section: Limitationsmentioning
confidence: 70%
“…However, research has shown that providing effective training and practice opportunities with technology for teachers is not straightforward (Alvarez et al, 2009;Ebert-May et al, 2011;Lawless & Pellegrino, 2007;Rienties, Brouwer, & Lygo-Baker, 2013;Stes et al, 2011). Some teachers prefer to learn a new VLE system using an auto-didactic approach: i.e.…”
Section: Training Needs For Technologymentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Technology is being increasingly used in tertiary education, as it is flexible and offers many possibilities to meet the needs of a large number of learners. In nursing education, E-learning is possibly the most important transformation in teaching since the move from hospital training to the higher education sector.…”
Section: Introductionmentioning
confidence: 99%
“…[14] The ability to use Information Communication Technology (ICT) by both learners and teachers has an impact to the integration of e-learning into existing teaching programs. [11] The use of technology in education requires a change in the educator's method of teaching, [15] with the literature indicating the positive impact of effective facilitation in higher education, [1,[16][17][18] particularly that online. [1,2,19] ICT can be defined as the use of hardware and software for the efficient management of information, and refers to the forms of technology that are used to transmit, store, create, share and exchange particular tasks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation